Finances of panchayats and status of own revenues in Telangana state: A critique - Reddy, M.Gopinath and Mohapatra, Bishnu Prasad (Indian Journal of Public Administration)
The Panchayati Raj Institutions (PRIs) have emerged as instruments of local government since 1992 with the passage of the 73rd Constitutional Amendment Act in India. In Telangana, the state government in the recent period has enacted State Panchayat Raj Act and constituted its first State Finance Commission (SFC). This article is a part of a larger study conducted in the context of the constitution of the first SFC. The article reveals that the own revenue of panchayats is quite low and transfer from the state and central governments constitute two key sources of these bodies. However, these bodies have faced various internal and external challenges while imposing and implementing taxes and fees to augment their sources of revenues. It is on this reality that this article suggests for the devolution of more taxes to PRIs by the SFC for strengthening their revenues and sharing at least 10% of the state$1 (Bs revenue to meet service delivery functions.- Reproduced s
Keywords: Fiscal decentralisaion, Taxes and non-taxes, State$1 (Bs own tax revenue, Telagana. s